Collective Transcendence of Aging People through Majelis Taklim: Challenging the Individual Assumptions of Gerotranscendence Theory - Abrori, Ahmad; Sajaroh, Wiwi Siti; Ahmad, Kanaya Aulia (Sekretariat Badan Moderasi Beragama dan Pengembangan Sumber Daya Manusia (BMBPSDM) Kementerian Agama RI, 2025)
This research examines the concept of elderly transcendence by questioning the individualistic assumptions in the Gerotranscendence theory developed by Lars Tornstam (1943-2016), a Swedish sociologist. Gerotranscendence is the shift experienced by elders from self-centered interests to broader, more transcendent perspectives. This theory states that such transcendence occurs through personal reflection and withdrawal from social life. However, in the context of Indonesia's collective culture, this research identified a problem: does transcendence depend only on individual reflection, or can it also be achieved through meaningful social interaction? To answer this question, the study used a phenomenological qualitative method involving 12 elderly people who are active in majelis taklim in urban Indonesia. Data were collected through in-depth interviews and participatory observation, then analyzed using a thematic approach. The results show that the elderly's participation in religious activities not only deepens their spiritual dimension, but also enriches life reflection and strengthens social relationships. The study resulted in the concept of “Collective Transcendence”, which asserts that achieving transcendence is not only through personal reflection but also supported by social and community interactions. As such, the findings encourage the development of Gerotranscendence theory to better suit collective culture and support religious community-based elderly welfare programs.